Design And Impedance Modeling Of Complementary Circular Loop FSS At 2.4ghz - Abd Aziz, Mohamad Zoinol Abidin; Abu Hussin, Farhana; Ahmad, Badrul Hisham; Suaidi, Mohamad Kadim; Md Fauzi, Noor Azamiah (Penerbit Universiti, UTeM, 2017)
-